Concurrent Decisions using Analytical Hierarchy Process at the Conceptual Design Stage - Arep@Ariff, Hambali; Minhat, Mohamad (Penerbit UTeM, 2010)
Considering the appropriate decision on design concept and material during early stage of development process is a crucial decision. Inappropriate decisions always lead to huge cost involvement and ultimately drive towards premature components or product failure. This paper presents the use of concurrent engineering principles and analytical hierarchy process (AHP) to assist designers in making the right decisions during the development process of products. The development of automotive bumper beam was chosen as a case study to illustrate the use of concurrent engineering principles and AHP in the making right decision during early stage of developments process. The paper reveals that glass fibre epoxy (25.8%), and design concept 6 (23.8%) are the best decisions during the development of automotive bumper beam at the conceptual design stage.